SKIN INFECTIONS IN DIABETES MELLITUS (DM) –A REVIEW (International Journal of Ayurveda and Pharma Research, 2020)
Diabetes Mellitus is the most common endocrine disorder and a various condition characterized by hyperglycemia as a consequence of defects in insulin secretion and variable degrees of insulin resistance. An estimated number of people with diabetes as projected to rise from 171 million in 2000 and 366 million in 2030. Skin disorders are present in 79.5% of patients with DM. Skin disorders, usually neglected and frequently under diagnosed among diabetic patients, are common complications and a broad spectrum of disorders in both type-1 and type-2 DM like- Prameha pidikas are Sharavika, Kachchapika, Jalini, Vidradhi Vinata, Alaji, Masurika, Sarshapika, Putrini and Savidarika, Dry skin, Fungal infection, Skin Tags, Ulcers, Diabetic foot etc. which can lead to major complication and revolve around multifactorical factor besides hyperglycemia and advanced glycation end products. Diabetics skin infections are correlate in the Ayurvedic literature describe of Prameha pidikas so that Prameha just described before the Kustha. Both the diseases are correlated with Kleda dusti. Therefore, the aim of this study is to perform a literature review to evaluate the various skin infections in DM patients. Ayurvedic classics as described many, Churnas, Guggulus, Gandhka yoga, Lohas, Kashayas, Leha, Ghritas Tailas, Lepas, etc. Herbal drugs -Vrana Shodhana and Ropana (Healing Agents) and Rakatmokshana for use in various Skin infections. The few of these herbal drugs have antifungal and anti bacterial action. The role of Ausadhi (Herbal Medicines), Ahara (dietary regimen) and Vihara (lifestyle) are equally or even more important to control blood sugar level as well as to prevent complications of this disease.